2009
DOI: 10.30674/scripta.67346
|View full text |Cite
|
Sign up to set email alerts
|

Necessary and impossible: on spiritual questions in relation to early induced abortion

Abstract: No matter how technically developed and medically sophisticated our society becomes, in the end we are all going to die. In other words, as human beings we are, from time to time, forced to deal with situations of existential significance. Existential and spiritual questions remain relevant—even in a country where most people­ have abandoned institutional forms of religion. But how do people­ deal with these questions? Sweden continues to uphold an extreme position, from a global perspective, when it comes to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Almost half of the women reported that they had done something special, or had wanted to do something special, to mark the abortion as an event, end the process, become reconciled with the situation, let off steam, or ask for forgiveness. From a psychology of religion perspective, this could be interpreted as a need for a symbolic or ritual closure [43,44]. In a country such as Sweden, where only a third of the population describe themselves as religious, this is particularly interesting [39].…”
Section: Discussionmentioning
confidence: 99%
“…Almost half of the women reported that they had done something special, or had wanted to do something special, to mark the abortion as an event, end the process, become reconciled with the situation, let off steam, or ask for forgiveness. From a psychology of religion perspective, this could be interpreted as a need for a symbolic or ritual closure [43,44]. In a country such as Sweden, where only a third of the population describe themselves as religious, this is particularly interesting [39].…”
Section: Discussionmentioning
confidence: 99%